2019
DOI: 10.18332/popmed/113392
|View full text |Cite
|
Sign up to set email alerts
|

Oral health status and related quality of life among tobacco factory and cotton ginning mill workers in Guntur city, Andhra Pradesh, India

Abstract: INTRODUCTION The study was carried out to assess and compare the oral health status and oral health-related quality of life among tobacco factory workers and cotton ginning mill workers in Guntur city, Andhra Pradesh, India. METHODS A cross-sectional study was carried among 160 tobacco factory workers and 160 cotton ginning mill workers aged 25-55 years. A simple random sampling methodology was used. The data were collected using a questionnaire and clinical examination. The questionnaire gathered information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…[ 14 ] A recent study conducted in the same geographical location as the present study reported relatively better oral health status and oral health related quality of life among spinning mill workers compared to workers from tobacco industry. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 14 ] A recent study conducted in the same geographical location as the present study reported relatively better oral health status and oral health related quality of life among spinning mill workers compared to workers from tobacco industry. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 ] Often oral health care facilities serve as the primary contact points for people in the diagnosis of general health conditions and in engaging the subjects to seek requisite medical care. [ 15 ] However, people from lower socioeconomic strata neglect dental care for a variety of reasons. [ 17 ] It is, therefore, important that primary care physicians play a proactive role in emphasizing on the maintenance of good oral hygiene, screening for basic oral health problems, and referring to oral health care professionals in case of necessity, especially for those from lower socioeconomic strata.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 ] There is a significant amount of literature on assessing oral health status and treatment needs across various populations in Andhra Pradesh state, such as schoolchildren, rural and older people, factory workers, and so on. [ 6 , 7 , 8 , 9 , 10 ] However, there are no data available on the oral health status of village volunteers, their treatment needs, or their utilization of dental services compared to other populations. Hence, this study was conducted to assess oral health status, treatment needs, and patterns of oral health services among village volunteers in Andhra Pradesh.…”
Section: Introductionmentioning
confidence: 99%